TINDAK TUTUR DIREKTIF DALAM DIALOG FILM TARUNG SARUNG KARYA ARCHIE HEKAGERY - St. Nurhalisa; Salam Salam; Idwati Idwati (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2023)
Directive Speech Acts in the Dialogue of the Film Tarung Sarung by Archie Hekagery. This research is a qualitative descriptive research that aims to: describe the form of directive speech acts contained in the dialogue of the film Tarung Sarong by Archie Hekagery and describe the function of directive speech acts contained in the dialogue of the film Tarung Sarung by Archie Hekagery. Data collection was carried out using free-involved listening techniques. The results of this research are related to directive speech acts seen from the aspects of form and function. In the dialogue of the film Tarung Sarong, six forms of directive speech acts are found, namely orders, requests, invitations, prohibitions, advice, and criticism. Judging from the function of directive speech acts, the dialogue in the film Tarung Sarung has various functions. The directive speech act form of command has the function of ordering, ordering, instructing, requiring, and permitting. The form of a request directive speech act has the function of requesting and begging. The directive speech act form of invitation has the functions of inviting, supporting, demanding and demanding. The form of prohibitive directive speech acts has the function of prohibiting and preventing. The directive speech act form of advice has the function of advising, suggesting and reminding. The directive speech act form of criticism has the function of reprimanding, cursing, getting angry and threatening.